2017
DOI: 10.6063/motricidade.7318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the task complexity on the performance of a Coincidence Timing Task of people with Down syndrome

Abstract: With the present study, we aimed to investigate the task complexity effects on the performance of a coincidence timing task in individuals with Down syndrome. The experimental group was consisted by 26 subjects with Down syndrome, 20 years old (± 5), and classified as mild or moderate in International Classification of Functioning and Health. Each participant in the experimental group was matched by in function of gender and age with a participant in a control group without Down syndrome. Both groups performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Studies using a coincident timing task with a control group (TD) and other diseases with altered posture and movement also verified better performance in the control group. Torriani‐Pasin et al [], de Mello Monteiro et al [], de Mello Monteiro et al [], and Bonuzzi et al [] found that the TD group was more efficient in sequences and errors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies using a coincident timing task with a control group (TD) and other diseases with altered posture and movement also verified better performance in the control group. Torriani‐Pasin et al [], de Mello Monteiro et al [], de Mello Monteiro et al [], and Bonuzzi et al [] found that the TD group was more efficient in sequences and errors.…”
Section: Discussionmentioning
confidence: 99%
“…The execution time was observed in each experimental stage and explained as follows: acquisition (A), retention (R), and transfer (T) [Trevizan et al, ]. A short‐term motor learning protocol was used based on previous studies by Gidley Larson and Mostofsky [], Torriani‐Pasin et al [], de Mello Monteiro et al [], de Mello Monteiro et al [], and Bonuzzi et al []. The motor learning protocol was organized through blocks of five trials each to ensure appropriate and representative evaluation of the participants' performances.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation